DiverCity - Global Cities as a Literary Phenomenon Toronto, New York, and Los Angeles in a Globalizing Age - Pooch, Melanie U. (Lettre, 2016)
Based on the structured analysis of selected North American novels, this work examines global cities as a literary phenomenon (»DiverCity«). By analyzing Dionne Brand's Toronto, »What We All Long For« (2005), Chang-rae Lee's New York, »Native Speaker« (1995), and Karen Tei Yamashita's Los Angeles, »Tropic of Orange« (1997), Melanie U. Pooch provides the connecting link for exploring the triad of globalization and its effects, global cities as cultural nodal points, and cultural diversity in a globalizing age as a literary phenomenon. Thus, she contributes to a global, interdisciplinary, and multi-perspectival understanding of literature, culture, and society.